Metode Tahsin Dalam Memperbaiki Bacaan Al-Quran - Irma, Eka Ade (Universitas Muhammadiyah Sumatera Utara, 2021)
This research is motivated by the problem of the lack of understanding of some students of SMP Al-Washliyah 30, Medan Labuhan on the importance of pronouncing makharijul letters and tajwid correctly when reading the Qur'an. Some students are used to listening to the teacher's explanation without repeating it at home. In addition, some students who have just entered this school have never studied tajwid at all. Because of that, the researchers considered it necessary to share the learning of tahsin in order to increase the understanding of students so that they are able to read the Qur'an properly and correctly. The definition of Tahsin itself is to recite or pronounce and remove each letter of the Qur'an from its place by giving its rights correctly. Or perfecting matters relating to the perfection of the pronunciation of the letters of the Qur'an from the aspect of their properties that are always attached to them and perfecting the pronunciation of the law of the relationship between one letter and another such as idzhar, idgham, ikhfa and so on. The research this time used qualitative data analysis techniques. This research was carried out for 10 days. With a meeting for one hour every day at 10:00 to 11:00 WIB. With the holding of the tahsin learning program for the students of SMP Al-Washliyah 30, it shows an increase in the reading ability of students who are starting to improve. Therefore, this kind of activity is expected to be sustainable.